Greetings the Mongondow Language at Molinow Sub-District - Ulfa Zakaria (Jambura Journal of Linguistics and Literature, 2022)
The purpose of this descriptive method with a qualitative approach study was to describe the greeting and the use of it, both self-name, related and non-related, as well as the factors that influence greeting in the Mongondow language in Molinow Village, Kotamobagu Barat District. This was based on the research problems. Further, the theory used in this study was the sociolinguistic theory where its data were the words used by speakers in greetings. Moreover, the data sources were from the environment of family, market, school, religious leaders, chiefs, and village head in the village and the Mongondow-Indonesian language dictionary as material to re-examine the greeting data. The techniques used were 1) observation, 2) interview, 3) listening, 4) recording, 5) note-taking, and 6) documentation. in data analysis, it used data reduction, data presentation, and concluding. The results of this study indicated that: (1) greetings in the Mongondow language have the forms of self-name greetings, 14 related i.e., Laki, Ba'ay, Ama', Ina', Guya-guyang, Ai-ai, Nanu'/Anu'/Epe', Uyo'/Uo', Poku'inaan, Poku'amaan, Ompu, Nunuton, Guya', and Utat. Non-related greetings consist of religious elders, chief, and general. (2) Factors that influence greetings in the Mongondow language, are: 1) permanent conditions consisting of social status, age, and gender, and 2) temporary conditions consisting of place, time, and topic of conversation